The Effect of Education on HIV/AIDS Prevention Housewives' Knowledge - Fathia Fakhri Inayati Said; Fenska Narly Makualaina; Nasrianti Nasrianti; Yestin Norita Joni; Hasnia Hasnia (Indonesian Journal of Global Health Research, 2026)
The number of HIV cases in Indonesia tends to increase Based on data from the Ministry of Health, the number of housewives infected with HIV has reached 35%. This figure is higher than HIV cases in other groups such as husbands of sex workers and MSM (men between sexes Objective to determine the effect of education about HIV/AIDS. HIV/AIDS Prevention on Housewives' Knowledge Method: This research is an experimental study with a one- group pretest-posttest design The population in this study was 55 The sampling technique used is purposive sampling, which involves selecting samples based on the researcher’s considerations that meet certain criteria. Results: There is an influence of providing education on HIV AIDS prevention for housewives in the AREMA Association, Jayapura Regency. The results of the analysis using paired sample t-test, P value of (0.000) < alpha (0.05) or the P value (0.000) is very small when compared to the alpha value (0.05). Conclusion: There is an influence of providing education on HIV AIDS prevention for housewives in the AREMA Association, Jayapura Regency.